Zimbabwe Economic Update, June 2021 : Overcoming Economic Challenges, Natural Disasters, and the Pandemic - Social and Economic Impacts - World Bank (World Bank, Washington, DC, 2021)
This third edition of the Zimbabwe Economic Update (ZEU) aims to provide both a current and historical background covering the pre-pandemic (2019) and pandemic (2020 to April 2021) period. The 2019-2020 period marked a very difficult time for the country as 2019 was clouded by a prolonged drought, unprecedented cyclone and turbulent economic reform period; while 2020 and early 2021 coincided with a global Coronavirus pandemic that further dampened prospects at both global and local levels.